Therapeutic Guidelines and Antimicrobial Resistance of Helicobacter Pylori in Patients with Peptic Ulcer at Tertiary Care Hospitals of Rawalpindi and Islamabad - Muhammad Bin Khurshid, Sadia Ahmed, Shehryar Javed, Muhammad Asher Javed, Muhammad Faizan, Huzaif Bangash, Hamza Sheraz, Ayesha Mudassar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to investigate the prevalence of antibiotic resistance among Helicobacter pylori isolates obtained from patients suffering from peptic ulcer disease in Rawalpindi and Islamabad, Pakistan, and to propose a novel anti-H. pylori therapy strategy for use in these locations. Methodology: A total of 132 H. pylori from the patients suffering with peptic ulcer disease were reported for clinical treatment in institutions in the twin Cities that provide tertiary care. Antibiotics such as ciprofloxacin, clarithromycin, amoxycillin, metronidazole, and tetracycline were tested on the isolates to determine their levels of susceptibility to these drugs. The Epsilometer test, often known as the E-test, is a quantitative disc diffusion method that is used to determine antibiotic sensitivity. This test was utilised for the purpose of verifying isolates. Results: The overall rate of resistance among H. pylori was found to be 27.9% for amoxycillin, 38.9% for clarithromycin, and 73.6% for metronidazole. 47 out of 132 isolates exhibited multiple drug resistance, with metronidazole, clarithromycin, and amoxycillin showing the highest frequency of two, three, and four drug resistance patterns. Ciprofloxacin had a low level of tetracycline resistance, ranging from 1.2 to 4%, whereas metronidazole resistance was substantial. In the population of Pakistan, the frequency of H. pylori resistance to metronidazole is quite high, whereas it is moderate in response to clarithromycin and amoxycillin, and low in response to ciprofloxacin and tetracycline. The rates of resistance to clarithromycin and amoxycilin were higher in Rawalpindi than they were in Islamabad. It is imperative, for the sake of the public’s health, that Pakistan make an adjustment to its policy regarding antibiotics, one that will permit the use of antibiotic rotation in the treatment of H. pylori. Keywords: Peptic ulcer, Helicobacter pylori, antibiotic susceptibility.